Eating habits of some Asian Labor Education Center participants and their implications to food service - Galutira, Gladys C. 1945-; Lavides, Violeta C. (1971)
Their descriptive study on eating habits of Filipino and other Asia participants to three Labor-Leadership Institutes at the Asian Labor Foundation Education Center (ALEC), was conducted from March to December 1970. Aspects of eating habits studied in this typically male group were meal patterns; food preferences on the basis of color, texture and flavor; and types and methods of preparation of foods. Other factors acceptability were also considered. The questionnaire-interview method was used. The subjects showed a diversity of eating practices. No single pattern could be drawn for the group nor any one country due to differences in ethnic groups and deeply-rooted family eating practices. A two-course meal was typical with variations in the kind and cookery of viand, vegetable, and cereal dishes. A strong preference for meat (especially chicken), fish (bangus, tanigue, labahita), and shrimp was shown, followed by fruits. Rice or bread accompanied each meal and vegetables were not popular. These findings pose no problem to the ALEC canteen since the meal pattern provides a variety of dishes, except vegetables, from which the selections may be made. However, additional information on acceptable types and methods of cooking vegetables will be most useful. Results likewise indicated an inherent human desire for variety not only of foods but also of food attributes and methods of cookery. Flavor appeared to affect food choice to a much greater extent than texture and color. Some differences were noted in the flavor preferences of Filipinos and other Asian delegates. In a decreasing order, while Filipinos choose swee0sour, salty, "hot" with chili, bland and dour flavors, other Asian delegates selected "hot" and curried; sweet-sour; salty; bland; garlic and sweet; and ginger flavors in the same order. A general trend was towards preference for "hot" and sweet-sour dishes. Among method of cookery, frying in vegetable oil was most popular. Creamed, broiled, bakes, boiled and steamed dishes were the choices of the Asian participants while Filipinos selected sauteed and broiled; creamed and boiled, steamed, baked and kinilaw and buttered dishes. Non-preferences for sauteed dishes by other Asians seemed to stem from non-familiarity than outright dislike since they ate vegetables cooked as such. Religion was shown to be a dominant factor which affected eating practices, especially among the non-Christians. These findings on food likes and dislikes, attributes and methods of cookery gave valuable information on which modifications of menu cycles and planning of a variety of acceptable dishes may be based. To prevent monotony in meal presentation and afford the delegates a homey feeling, meals featuring special dishes may be initiated. Information on religious restrictions made the investigator more understanding such groups and prompted definite steps towards meeting their needs. Other modifications, particularly in methods of cookery, were instituted. Other areas in need of improvement were revealed in this study. Additional knowledge on eating practices of this and other groups should be gained. The dietitian should be more fully exposed to these delegates in their locale in order to understand eating habits and attitudes about foods. Hence, it is strongly recommended that the dietitian be included in the staff exchange programs with other labor centers in Asia.
Thesis (M. S.)--University of the Philippines, Quezon City.
Typescript.
Vita.
Keywords: Food habits -- Philippines; Food preferences